Incidence of Post Dural Puncture Headache in Our Set Up with Quincke Spinal Needle: An Observational Crossectional Study - Swapnil Meshram1 , Pratibha Deshmukh2 , Parag Sabale1 , Nandkishor Bankar3 , Vijay C. Chandak (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Post-dural puncture headache (PDPH) is an iatrogenic complication associated with spinalanaesthesia. The occurrence of PDPH is determined by different factors. They are sex, age, pregnancy, pastPDPH history, needle tip shape and needle size, bevel orientation, number of attempts, and approach usedfor lumbar puncture. We conducted the present study to find the incidence of PDPH.Material and Method: After ethics committee approval, we observed 500 patients who had undergonesurgery for lower abdomen and lower limb. Patients were randomly divided in Group A and Group B 250patients in each group and received spinal anaesthesia via 23 and 25 quincke spinal needle respectively.They were followed post operatively regularly for development of any signs and symptoms of post dualpuncture headache, which was end point of study.Results: Out of 500 patients 6 patient developed PDPH. The incidence was 1.2%. There was no statisticallysignificance with sex, number of attempts and guage of spinal needle.Conclusion: In our series the incidence was 1.2% which is far less than other studies. Taking intoconsideration cost effectiveness & success rate we feel that in our setup we can continue with use of 23 &25-gauge quincke needle.